Question search with different information retrieval model - Lee, Qian Hui. (2012)
Online communities such as forums are valuable information sources where knowledge is accumulated by interactions between people. Search services (e.g. keyword search) provided by online community sites are often, however, quite poor. Most of current forum services support only simple keyword matching search.